Genetic diversity and population structure analysis of Lateolabrax maculatus from Chinese coastal waters using polymorphic microsatellite markers - Wei Wang (Nature Portfolio, 2021)
Abstract In order to provide valuable guidelines for the conservation of germplasm of Lateolabrax maculatus, the genetic diversity and population structure analysis were evaluated for eight geographic populations along coastal regions of China, using 11 microsatellite DNA markers. The genetic parameters obtained showed that, eight populations can be clustered into two groups, the Northern group and the Southern group, concordant with their geographical positions. The UPGMA tree constructed according to the Nei’s genetic distance along with the structure analysis and discriminant analysis of principal component also supported this result. This might be explained by the geographic separation and the divergent environmental conditions among the populations. It's worth noting that, QD (Qingdao) population from northern area was assigned to the Southern group and showed a close genetic relationship and similar genetic constitution with the southern populations. We speculated that large scales of anthropogenic transportation of wild fries from QD populations to the southern aquaculture areas in history should be the primary cause. The populations from GY (Ganyu), RD (Rudong) and BH (Binhai) had higher genetic diversity and showed limited genetic exchange with other populations, indicating better conservation of the natural resources in these regions. All populations were indicated to have experienced bottleneck events in history.